ANALISA SIMULASI KERUSAKAN IMPELLER PADA POMPA SENTRIFUGAL AKIBAT KAVITASI - Rosid Rosid; Jojo Sumarjo (University of Muhammadiyah Jakarta, 2017)
Centrifugal pumps are widely used equipment in a variety of industrial applications and some other sectors. The pump works by converting mechanical energy into kinetic energy or press. Pressure at the pump increases at low pressure (lower than atmospheric pressure). This research is to know the analysis of cavitation on water purification process at Unit Water Treatment At PT. XXX in Karawang. The analysis was performed on the centrifugal pump to calculate the speed of the suction pipe, the speed of the compressive pipe and calculate the Net Positive Suction Head (NPSH) to determine whether the pump worked by cavitation and analyze the speed with the Solidworks sofwar simulation. Creating computer modeling and simulation of suction pipe speed mechanism and speed of pipe press with Sofwar Solidworks. Counting head losses on suction pipe and head losses on press pipes. Calculate the Net Positive Suction Head (NPSH) to determine whether the pump that works is affected by Cavitation. This study is expected to provide information and reviews for industries using centrifugal pumps for the design of suction pipes and press pipes to reduce damage to impeller due to cavitation. As reference material for the user of centrifugal pump for redesign of impeller. Available NPSH is 2.13 and NPSH is required 0.5 to avoid cavitation due to the available NPSH value greater than required NPSH value.